OUTCOME OF SPINE FIXATION FOR UNSTABLE FRACTURES AT DORSOLUMBAR JUNCTION INCLUDING FRACTURED VERTEBRAE IN PEDICULAR SCREW FIXATION - Naseer Hassan; Muhammad Gulzar khan; Anwar Imran; Sardar Sohail Afsar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Injury of the spinal cord with loss of neurological function is the most devastating life-changing injury. Each year a large number of Pakistani population sustain spinal injuries. Studies on spinal injuries have been published in Pakistan but the exact incidence of spinal injuries in Pakistan is still unknown. Objective: To assess the outcome of spine fixation for unstable fractures at dorsolumbar junction including fractured vertebrae in pedicular screw fixation Methodology: This prospective multi-centre study was conducted at Department of Orthopaedics and Spine Surgery, Qazi Hussain Ahmed Medical Complex, Nowshera and other private medical centers in Peshawar Pakistan, from August 2021 to August 2022. A total of 130 patients were included in this study with single level fractures from D11 to L2. Complete history and physical examination were done in each case. X-rays of the whole spine and MRI of dorso-lumbar region were done in all cases. Patients were evaluated both radiologically and clinically. All these parameters were measured before surgery immediately after surgery and at 6 months post-operatively. The data was analyzed using SPSS soft ware version 23. Results: A total of 130 patients were included in this study. The mean age (SD) of the enrolled patients was 32.8 (±2.11) years. There were 97 (74.62%) male patients while the female patients were 33 (25.38%). A statistical significant improvement was observed post-operatively in Cobb angle, anterior vertebral height, posterior vertebral height and sagittal index. (p<0.05). Statistical significant improvement in Oswestry disability index (ODI) and reduction in VAS was observed in our study. (p<0.05). The post-operative complications were observed in only 12 (9.24%) Patients. Conclusion: In our study, Trans-pedicular screw fixation including the fractured vertebrae gave excellent radiological and clinical outcome. It improved the biomechanical stability by giving extra pedicle for fixation which shorten the fixation segment and also helped in reduction and deformity correction. We therefore strongly recommend fixation of the fractured vertebra in trans-pedicular screw fixation of dorso-lumbar spine fractures.”